Design analysis of open and ducted propellers in UAV application - Anies Faziehan Zakaria; Mohamed Fariz Mohamed Nasir; Azfarizal Mukhtar; Muhd Nazhif Ridzuan (Penerbit Universiti Kebangsaan Malaysia, 2022)
The aim of the study was to determine the feasibility of implementing a ducted propeller system for small scale drones. 5” propeller drones are common in first person view (FPV) drone racing and cinematography, increasing the likelihood of injury due to untrained pilots, of which the majority are laceration injuries due to the propeller blades. Furthermore, the addition of a duct improves the thrust output of the entire system. A few key parameters are identified, of which were manipulated to determine the optimum values through a series of ANSYS Fluent CFD simulations. Introducing a duct is shown to reduce the lift a propeller produces; however, the reduction is offset by the lift generated by the duct. Blade tip clearance was investigated, with the optimum value found to be 0.25 mm, producing the most lift from the duct and least reduction of propeller lift, and with thrust outputs up to 35.568% more in some cases compared to open propeller. It was observed that increasing the BTC significantly reduced duct lift. Diffuser length simulations provided unconclusive results, with the duct lift varying depending on the diffuser length. However, the optimum diffuser length was determined to be 65 mm with respect to thrust outputs. In comparison, inlet lip radius shows a clear pattern, deviating from the optimum value of 16.5 mm reduces the duct lift produced, with smaller values severely decreasing performance.